Some new approaches to the study of the Earth's magnetic field reversals - G. Consolini; P. De Michelis (Annals of Geophysics, 2003)
Paleomagnetic studies clearly show that the polarity of the magnetic fi eld has been subject to reversals. It is
generally assumed that polarity intervals are exponentially distributed. Here, the geomagnetic polarity reversal
record, for the past 166 Ma, is analysed and a new approach to the study of the reversals is presented. In detail, the
occurrence of 1/f-noise in the Power Spectral Density (PSD), relative to geomagnetic fi eld reversals, the existence
of a Zipf's law behaviour for the cumulative distribution of polarity intervals, and the occurrence of punctuated
equilibrium, as shown by a sort of Devil's staircase for the reversal time series, are investigated. Our results give
a preliminary picture of the dynamical state of the geomagnetic dynamo suggesting that the geodynamo works in
a marginally stable out-of-equilibrium confi guration, and that polarity reversals are equivalent to a sort of phase
transition between two metastable states.